Measuring parents' acceptance of non-national immunization program vaccines for children and its influencing factors during the COVID-19 pandemic in Shanghai, China. Issue 5 (30th November 2022) - Wu, Linlin; Huang, Zhuoying; Guo, Xiang; Liu, Jiechen; Sun, Xiaodong
ABSTRACT: This study aimed to understand the willingness of and affecting factors of non-national immunization program (non-NIP) vaccines among children's parents during the COVID-19 era in Shanghai, China. A cross-sectional survey was conducted with parents who attended vaccination clinics in four out of 16 districts in Shanghai, China. Data was obtained using a self-administered structured questionnaire. A multivariate logistic regression model was used to analyze factors associated with vaccination acceptability. In total, 1691 valid questionnaires were obtained. Of the participants, 69.5% (1, 176/1, 691) reported being interested in non-NIP vaccines for their children. Further, respondents were more likely to be willing to get non-NIP vaccines for their children if they had an income of 10, 000–20, 000CNY or more, an educational level of college or above, and if getting the vaccination was moderately convenient or convenient. Respondents were less likely to be willing to get the vaccines if they were in the 30–39 age group and had moderate or low satisfaction with the vaccine. Many parents are willing to get non-NIP vaccines for their children. However, some demographic factors, perceived convenience and satisfaction of vaccination, perceived necessity, safety and price barrier of non- NIP influenced the acceptability of non-NIP vaccines in Shanghai. Our findings can help guide future efforts to increase non-NIP vaccines acceptability.